Second-Sound Waves in Cryocrystals - Khodusov, V.D.; Blinkina, A.A. (Український фізичний журнал, 2010)
The self-coordinated values of parameters of cryocrystals of orthodeuterium, parahydrogen, and neon (temperature, isotope concentrations, and the sizes of samples), which define the range of second-sound waves existence, are found. The limiting isotope concentrations, below which the propagation of second-sound waves is possible, are established. The sizes of samples, starting from which their increase does not essentially influence the damping of second-sound waves are found. The results are presented in threedimensional plots. Знайдено узгодженi значення параметрiв крiокристалiв ортодейтерiю, параводню та неону (температури, концентрацiї iзотопiв, домiшок та розмiрiв зразкiв), що визначають область iснування хвиль другого звуку. Встановлено граничнi концентрацiї iзотопiв, нижче за якi можливе поширення хвиль другого звуку, а також визначено розмiри зразкiв, починаючи з яких їх збiльшення не впливає на загасання хвиль другого звуку. Результати наведено у виглядi тривимiрних графiкiв.